If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 126 + -7x = 11x + 20 Reorder the terms: 126 + -7x = 20 + 11x Solving 126 + -7x = 20 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 126 + -7x + -11x = 20 + 11x + -11x Combine like terms: -7x + -11x = -18x 126 + -18x = 20 + 11x + -11x Combine like terms: 11x + -11x = 0 126 + -18x = 20 + 0 126 + -18x = 20 Add '-126' to each side of the equation. 126 + -126 + -18x = 20 + -126 Combine like terms: 126 + -126 = 0 0 + -18x = 20 + -126 -18x = 20 + -126 Combine like terms: 20 + -126 = -106 -18x = -106 Divide each side by '-18'. x = 5.888888889 Simplifying x = 5.888888889
| 2x^3+16x+18x^2=0 | | (x+3)/2=(x-3)/5 | | -3*-3-3-c=0 | | (x-2)/3=(x+1)/4 | | 11xX-166=4xX-12 | | x+21+4x=-19-4x-23 | | 7x+3=-81 | | integraly=lnx | | (-3)-(-5)=x | | 3x+2(.5x-1)=18 | | 3X+3X+1=108 | | 7(n-5)-(2-n)= | | (a+4)(a+5)= | | 7x+2=-61 | | 9(n+7)+3(n-2)= | | 4x^2-3x=2x-x^2 | | (-3)-(-5)= | | 7(n+1)+7(n+5)= | | -2(a-3b)-(2a-b)= | | 3x+99=-99-9x | | (x-2)-x(x-2)=0 | | 0.3333(15x+975)=4000 | | 5-2p=15-3p | | (5x+3)+(5x-3)+90=180 | | -p*p= | | y^2-2y+1=16 | | 0.125(x+230)=200 | | -2(3x-5)= | | 2y+16=180 | | 2(2y+16)=7y-7 | | 188-5x=40x+18 | | (3z+5)+(2z-10)+90=180 |